PENGEMBANGAN KURIKULUM PROGRAM UNGGULAN DI SD MUHAMMADIYAH KLECO KOTAGEDE - Gesang Setyo Aji (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2019)
The crisis in the dimension of the quality of human resources and the crisis in the field of the identity and morality of Indonesian people is a troubling education problem in Indonesia. This paper seeks to convey views about managerial efforts in curriculum development for leading programs in the context of Muhammadiyah Elementary schools. This study uses a qualitative field research approach at SD Muhammadiyah Kleco. The results of the study show: The implementation of the management of Leading Program Development at the Muhammadiyah Elementary School in Kleco, Kotagede, Yogyakarta is not much different from the management of PAI curriculum in other schools which includes planning, organizing, implementing, and evaluating curriculum activities. The results achieved from the implementation of the Featured Program at SD Muhammadiyah Kleco Kotagede are the increasing knowledge and abilities of students, especially in the aspects of the Qur'an. In addition, the implementation of the Featured Program also had a positive impact on student achievement in the religious field and besides that it was also a branding force for the Muhammadiyah Kleco Elementary School in Yogyakarta to compete in the education market especially in the city of Yogyakarta.